Electrografting of isophthalic acid monolayer and covalent attachment of antibody onto carbon surfaces: Construction of capacitive biosensor for methotrexate detection. (1st December 2021) - Mwanza, Daniel; Phal, Sereilakhena; Nyokong, Tebello; Tesfalidet, Solomon; Mashazi, Philani
Abstract: In this study, a 5-diazonium isophthalic acid was synthesized and electrografted onto glassy carbon (GCE) and screen-printed carbon (SPCE) electrodes. SPCE was used to demonstrate fabrication of a miniature device and to compare with conventional glassy carbon electrodes. The isophthalic acid (IPA) electrografted thin film was used for the immobilization of anti-methotrexate antibody (Ab) using carbodiimide activation chemistry to form antibody modified surfaces, GCE-IPA-Ab and SPCE-IPA-Ab. The GCE -IPA-Ab and SPCE-IPA-Ab surfaces were used as capacitive biosensors for the detection of methotrexate (MTX) in phosphate buffer (pH 7.4) using capacitive electrochemical impedance spectroscopy (EIS). The EIS data was analyzed using singular value decomposition (SVD). Principal component regression analysis gave R 2 values of 0.99 for both the GCE-IPA-Ab and SPCE-IPA-Ab surfaces. The detection limit from the calibration curve of the GCE-IPA-Ab and SPCE-IPA-Ab was calculated to be 7.0 pmol.L −1 and 5.5 pmol.L −1, respectively.